Women Component Plan at the Village Panchayat Level in Kerala: Does it Live Up to its Promise? - Nisha Velappan Nair AND John S. Moolakkattu (Indian Journal of Gender Studies, 2014)
This article looks at the performance of the Women Component Plan (WCP) introduced at the local level in Kerala to encourage participatory planning by studying the experience of five village pan- chayats over a 10 year reference period. There has been a marked difference among projects carried out under the WCP and general sec- tor projects and projects meant for Scheduled Castes in expenditure efficiency. The article also looks at the nature of projects implemented, the extent of participation of women members in their design and exe- cution, and the opinion of elected representatives on the usefulness of the WCP